Internal rot detection with the use of low-frequency flaw detector = Wykrywanie murszu wewnętrznego za pomocą defektoskopu niskoczęstotliwościowego - Proskórnicki, Marek; Ligus, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The issue of rot detection in standing timber or stocked wood is very important in forest management. Rot flaw detection used for that purpose is represented by invasive and non-invasive devices. Non-invasive devices are very accurate, but due to the cost and complicated operation they have not been applied on a large scale in forest management. Taking into account the practical needs of foresters a prototype of low-frequency flaw was developed. The principle of its operation is based on the difference in acoustic wave propagation in sound wood and wood with rot.
Keywords: drewno zmurszałe; defektoskopia murszowa; gospodarstwa leśne; defektoskop niskoczęstotliwościowy; internal rot; flaw detection methods; forest holdings